Preparation process of marine concrete structure crack repair material

By adding anti-carbonization agents and thermal crackers to the crack repair materials of marine concrete structures, the problem of insufficient carbonization resistance of sulfoaluminate cement-based repair materials is solved, and efficient anti-carbonization and later strength improvement of repair materials is achieved.

CN119430818BActive Publication Date: 2025-04-18QINGDAO AGRI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410759072.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-04-18
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The crack repair materials in offshore concrete structures have problems with insufficient carbonization resistance, resulting in a decrease in the strength and corrosion resistance of the repair materials.

Method used

A preparation process for crack repair materials for marine concrete structures is adopted. By adding anti-carbonization agents and thermal crackers to sulfaaluminate cement-based repair materials, the anti-carbonization ability and later strength of the repair materials are improved. The anti-carbizing agent consists of tricalcium silicate particles and a coated film layer coated with calcium carbide slag particles. It can consume carbon dioxide and form calcium carbonate to block the erosion of carbon dioxide. Thermal cracking agent is composed of graphene and paraffin, which can prevent the uneven distribution of hydration heat and reduce the generation of cracks.

Benefits of technology

It effectively improves the carbonization resistance and later strength of sulfaluminate cement-based repair materials, enhances the durability and crack resistance of repair materials, and avoids the strength of repair materials in a carbonized environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430818B_ABST
    Figure CN119430818B_ABST
Patent Text Reader

Abstract

This invention relates to the field of marine concrete preparation technology, specifically disclosing a preparation process for a marine concrete structure crack repair material. The process includes the following steps: (1) using sulfoaluminate cement, fine aggregate, inorganic filler, anti-carbonation agent, retarder, water-reducing agent, and defoamer as raw materials. The above raw materials are mixed evenly, then water is added and stirred until homogeneous to obtain the repair material. The anti-carbonation agent is prepared using the following method: (2) Shellac is dissolved in anhydrous ethanol, then calcium carbide slag powder is added and mixed evenly to form a suspension. (3) The suspension is sprayed onto rolling tricalcium silicate particles, evenly coated, and then rolled and heated to dry, resulting in granular anti-carbonation agent. The above repair material not only effectively improves the anti-carbonation ability of sulfoaluminate cement, but also has the function of self-sealing carbon dioxide and moisture transport channels, increasing the later strength of the repair material, and improving the durability of the repair material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of marine engineering concrete preparation, and in particular to a preparation process of a marine engineering concrete structure crack repair material. Background Art

[0002] As a material widely used in the field of construction engineering, concrete is bound to crack during use. In severe cases, the cracks may even penetrate the entire concrete structure. Marine concrete refers to concrete that serves on the seashore, in seawater, or in an environment affected by sea breeze, and is affected by seawater or sea breeze. It is mainly used in the construction of coastal and offshore projects, such as seawalls, tide gates, cross-sea bridges, and offshore platforms. Cracks are a common disease of marine concrete structures, which often lead to reduced bearing capacity, durability, and waterproof performance of marine concrete structures. In particular, the service environment of marine concrete structures is more severe than that of ordinary environments. The presence of cracks will accelerate the corrosion of the steel bars, further leading to a decrease in the bearing capacity of the concrete structure.

[0003] Timely repair of cracks in marine concrete structures is an important measure to avoid more serious consequences. The current main repair method is to pour cement-based repair mortar into the cracks. Since crack repair is an emergency repair project, the repair mortar needs to harden quickly and provide high early strength. Sulphoaluminate cement not only has the characteristics of fast hardening, early strength and high frost resistance, but also has good resistance to corrosion by seawater, chloride salts, sulfates, etc., and is suitable as a repair material for cracks in marine concrete structures. However, sulphoaluminate cement has poor carbonation resistance. This is because the main hydration product of sulphoaluminate cement, calcium sulfoxide, has a low alkalinity and is easily carbonized and decomposed under the erosion of carbon dioxide, resulting in a decrease in the strength and corrosion resistance of the repair material in the concrete cracks, or even falling off. Summary of the invention

[0004] In view of the above problems, the present invention provides a preparation process of a marine concrete structure crack repair material, which not only effectively improves the carbonation resistance of sulphoaluminate cement, but also has the function of self-blocking carbon dioxide and water transmission channels, increasing the later strength of the repair material, and improving the durability of the repair material. Specifically, the technical solution of the present invention is as follows.

[0005] A preparation process of a marine concrete structure crack repair material comprises the following steps:

[0006] (1) Take 120-140 parts by weight of sulphoaluminate cement, 190-250 parts by weight of fine aggregate, 50-75 parts by weight of inorganic filler, 45-60 parts by weight of anti-carbonation agent, 0.1-0.3 parts by weight of retarder, 1.5-2.2 parts by weight of water reducer, and 0.35-0.7 parts by weight of defoamer as raw materials. Mix the above raw materials, add clean water, and stir evenly to obtain the repair material. The anti-carbonation agent is prepared by the following method:

[0007] (2) Dissolve shellac in anhydrous ethanol, then add carbide slag powder and mix well to form a suspension.

[0008] (3) Spraying the suspension on the rolling tricalcium silicate particles, and continuing to roll and heat to dry after uniform coating, to obtain the anti-carbonization agent in granular form.

[0009] Furthermore, in step (1), the fine aggregate includes at least one of river sand, machine-made sand, etc. Optionally, the particle size of the fine aggregate is between 0.1 and 0.25 mm.

[0010] Furthermore, in step (1), the inorganic filler includes at least one of fly ash, silica fume, slag powder, calcium carbonate powder, metakaolin, etc. Optionally, the fineness of the slag powder, calcium carbonate powder, and metakaolin is between 200 and 300 meshes.

[0011] Furthermore, in step (1), the retarder includes at least one of borax, citric acid, sodium gluconate, tartaric acid, etc.

[0012] Furthermore, in step (1), the water reducer includes at least one of a polycarboxylic acid water reducer, a naphthalene-based water reducer, a lignin sulfonate-based water reducer, and the like.

[0013] Furthermore, in step (1), the defoaming agent includes at least one of a silicone defoaming agent, a polyether defoaming agent, and the like.

[0014] Furthermore, in step (1), the clean water is added according to a water-cement ratio of 0.37-0.44, and any other suitable water-cement ratio may be used as required.

[0015] Furthermore, in step (1), the raw materials also include 23-28 parts by weight of an anti-thermal cracking agent. The anti-thermal cracking agent is prepared by the following process: adding graphene to heated and melted paraffin liquid, mixing evenly, cooling, and then crushing to obtain the anti-thermal cracking agent in powder form.

[0016] Furthermore, the mass ratio of the graphene to the paraffin liquid is 1:1.5-1.8, and the melting point of the paraffin wax does not exceed 60° C. Optionally, the fineness of the anti-thermal cracking agent is 80-120 meshes.

[0017] Furthermore, in step (2), the mass fraction of shellac in the anhydrous ethanol is 3.5-6%.

[0018] Furthermore, in step (2), the content of carbide slag powder in the suspension is 0.25-0.4 g / ml. Optionally, the fineness of the carbide slag powder is 300-400 mesh.

[0019] Furthermore, in step (3), the material-liquid ratio of the tricalcium silicate particles to the suspension is 1 g: 0.8-1.1 ml. Optionally, the particle size of the tricalcium silicate particles is 0.2-0.3 mm.

[0020] Furthermore, in step (3), the heating temperature is 60-70° C. and the heating time is 20-35 min.

[0021] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0022] The concrete structure crack repair material with sulphoaluminate cement as the cementitious material has the problem of insufficient carbonation resistance. The anti-carbonation agent added in the present invention can effectively consume the carbon dioxide entering the repair material, alleviate the problem that the hydration products of sulphoaluminate cement undergo carbonization reaction and decomposition under the erosion of carbon dioxide, and improve the anti-carbonation ability of the repair material. This is because: the anti-carbonation agent is formed by tricalcium silicate particles and a coating layer containing carbide slag particles coated on its surface. After carbon dioxide and water enter the sulphoaluminate cement-based repair material, the acidic solution formed will corrode the carbide slag particles that are more prone to reaction and produce an acid-base reaction. On the one hand, the acidic environment is consumed, which can reduce further erosion. On the other hand, the calcium ions provided by the carbide slag react with the carbonate ions formed by carbon dioxide to form calcium carbonate, which realizes the solidification of carbon dioxide, blocks the erosion process of carbon dioxide, and makes carbon dioxide lose the ability to further erode. The above process gives the repair material a first-tier anti-carbonation ability. When the carbide slag is consumed by the reaction, causing the coating on the surface of the tricalcium silicate particles to be gradually destroyed and exposed, the tricalcium silicate is hydrated after contacting with water to form a hydration product, calcium hydroxide and a hydrated calcium silicate gelling component, so that the anti-carbonization agent is activated by the above process to exert the second-tier anti-carbonization ability. On the one hand, the calcium hydroxide can continue to neutralize and solidify carbon dioxide like the carbide slag. On the other hand, the hydrated calcium silicate gelling component can play a role in sealing the transmission channel of carbon dioxide and water, especially the interface between the repair material and the crack that is easy to produce the transmission channel, thereby preventing the further penetration of carbon dioxide and water, so that the repair material of the present invention has the function of self-blocking the transmission channel of carbon dioxide and water. The second-tier anti-carbonization ability is given to the repair material through the above process, which effectively enhances the anti-carbonization ability of the sulphoaluminate cement repair material. In addition, the formation of the hydrated calcium silicate gelling component also has the effect of repairing microcracks in the repair material and increasing the later strength of the repair material.

[0023] In addition, the repair material of the present invention is also mixed with the anti-thermal cracking agent, which helps to prevent the problem of cracks in the hydration process of sulphoaluminate cement. This is because the hydration rate of sulphoaluminate cement is fast, and a large amount of heat is released in a short time. The temperature of the central part can even be as high as 80°C, and the temperature difference between different parts can easily cause cracks. The anti-thermal cracking agent of the present invention is composed of graphene and paraffin. The paraffin that melts under the action of hydration heat can be distributed in the repair material to construct a hydrophobic system, which not only helps to prevent the entry of external moisture, but also helps to reduce the contact between the hydration products of sulphoaluminate cement and carbon dioxide and water, thereby blocking the conditions for carbonization and constructing a second-tier anti-carbonization ability. At the same time, the melting of the paraffin can effectively consume the hydration heat and promote the uniformity of heat distribution. The graphene has good thermal conductivity, promotes the uniformity of the distribution of temperatures in various parts of the repair material, and accelerates the heat dissipation capacity of the repair material to prevent the accumulation of hydration heat in the repair material. The effects of the above aspects can effectively reduce the driving force for crack generation and reduce the generation of thermal cracks in the repair material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0025] Figure 1 This is a carbonization resistance test diagram of the following Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0027] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.

[0028] Example 1

[0029] A preparation process of a marine concrete structure crack repair material comprises the following steps:

[0030] (1) Shellac is added to anhydrous ethanol and stirred to form a 4% by mass shellac ethanol solution, and then 400-mesh calcium carbide slag powder is added and ultrasonically dispersed for 10 minutes to obtain a suspension for use, wherein the content of the calcium carbide slag powder is 0.3 g / ml.

[0031] (2) Spray the suspension in the rolling tricalcium silicate particles (particle size 0.2-0.3 mm) at a material-liquid ratio of 1 g:1 ml. Continue rolling for 2 minutes after spraying, then continue rolling and heat to 70°C for 25 minutes. After completion, cool to room temperature to obtain a granular anti-carbonization agent for use.

[0032] (3) Take 131 parts by weight of rapid hardening sulphoaluminate cement, 230 parts by weight of river sand fine aggregate with a particle size between 0.1 and 0.2 mm, 50 parts by weight of inorganic filler (including 30 parts by weight of fly ash and 20 parts by weight of silica fume), 52 parts by weight of the anti-carbonation agent prepared in this example, 0.2 parts by weight of retarder (borax), 2 parts by weight of polycarboxylate water reducer, and 0.5 parts by weight of silicone defoamer.

[0033] (4) The rapid-hardening sulphoaluminate cement, fine sand aggregate, inorganic filler and anti-carbonation agent are mixed and stirred for 2 minutes, and then the retarder, setting retarder and defoamer are added, and clean water is added according to a water-cement ratio of 0.42 and stirred evenly to obtain a sulphoaluminate cement-based repair material.

[0034] The sulphoaluminate cement-based repair material prepared in this example was poured into a mold, demoulded after hardening and then placed in a standard curing box for curing for 3 days. The compressive strength of the obtained specimens was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-1999). In addition, the carbonization resistance of the specimens prepared in the same batch was tested (reference Figure 1 ): The obtained specimens were placed in a carbonization box (temperature 20±2℃, relative humidity 70±5%, CO2 concentration 20±3%) for carbonation for 7d and 28d respectively, and then the compressive strength of the obtained specimens was tested and the strength retention rate was calculated. Among them: the 7d strength retention rate is the ratio of the 7d compressive strength to the 3d compressive strength, and the 28d strength retention rate is the ratio of the 28d compressive strength to the 3d compressive strength. The results are shown in Table 1.

[0035] Table 1

[0036] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 67.19MPa 97.05% 113.36%

[0037] Example 2

[0038] A preparation process of a marine concrete structure crack repair material comprises the following steps:

[0039] (1) Shellac is added to anhydrous ethanol and stirred to form a 6% by mass shellac ethanol solution, and then 400-mesh calcium carbide slag powder is added and ultrasonically dispersed for 10 minutes to obtain a suspension for use, wherein the content of the calcium carbide slag powder is 0.25 g / ml.

[0040] (2) Spray the suspension on the rolling tricalcium silicate particles (particle size 0.2-0.3 mm) at a material-liquid ratio of 1 g of the suspension to 0.8 ml of the suspension. Continue rolling for 2 minutes after spraying, then continue rolling and heat to 60°C for 35 minutes to dry. After completion, cool to room temperature to obtain a granular anti-carbonization agent for use.

[0041] (3) After heating paraffin to 55°C and melting it, graphene is added to the resulting paraffin liquid in a mass ratio of 1.8:1. Rapidly stir until the graphene is evenly dispersed in the paraffin liquid and then cool to room temperature. Then, the obtained solid is ball-milled and passed through a 120-mesh sieve to obtain a thermal cracking inhibitor for later use.

[0042] (4) Take 120 parts by weight of rapid hardening sulphoaluminate cement, 190 parts by weight of river sand fine aggregate with a particle size between 0.1 and 0.25 mm, 60 parts by weight of inorganic filler (including 40 parts by weight of fly ash and 20 parts by weight of 300-mesh slag powder), 45 parts by weight of the anti-carbonation agent prepared in this example, 23 parts by weight of the anti-thermal cracking agent prepared in this example, 0.1 parts by weight of retarder (sodium gluconate), 1.5 parts by weight of polycarboxylate water reducer, and 0.35 parts by weight of silicone defoamer.

[0043] (5) The rapid hardening sulphoaluminate cement, fine sand aggregate, inorganic filler, anti-carbonation agent and anti-thermal cracking agent are mixed and stirred for 2 minutes, and then the retarder, retarder and defoamer are added, and clean water is added according to a water-cement ratio of 0.37 and stirred evenly to obtain a sulphoaluminate cement-based repair material.

[0044] The 3d compressive strength, 7d strength retention rate and 28d strength retention rate of the sulphoaluminate cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The results are shown in Table 2.

[0045] Table 2

[0046] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 72.44MPa 99.71% 102.43%

[0047] Example 3

[0048] A preparation process of a marine concrete structure crack repair material comprises the following steps:

[0049] (1) Shellac is added to anhydrous ethanol and stirred to form a 3.5% by mass shellac ethanol solution, and then 300-mesh calcium carbide slag powder is added and ultrasonically dispersed for 10 minutes to obtain a suspension for use, wherein the content of the calcium carbide slag powder is 0.4 g / ml.

[0050] (2) Spray the suspension on the rolling tricalcium silicate particles (particle size 0.2-0.3 mm) at a material-liquid ratio of 1 g:1.1 ml of the suspension. Continue rolling for 2 minutes after spraying, then continue rolling and heat to 65°C for 30 minutes to dry. After completion, cool to room temperature to obtain a granular anti-carbonization agent for use.

[0051] (3) After heating paraffin to 60°C and melting it, graphene is added to the resulting paraffin liquid in a mass ratio of 1.5:1. Rapidly stir until the graphene is evenly dispersed in the paraffin liquid and then cool to room temperature. Then, the obtained solid is ball-milled and passed through an 80-mesh sieve to obtain a thermal cracking inhibitor for later use.

[0052] (4) Take 140 parts by weight of rapid hardening sulphoaluminate cement, 250 parts by weight of machine-made sand fine aggregate with a particle size of 0.1-0.2 mm, 75 parts by weight of inorganic filler (calcium carbonate powder with a fineness of 200 mesh), 60 parts by weight of the anti-carbonation agent prepared in this example, 28 parts by weight of the anti-thermal cracking agent prepared in this example, 0.3 parts by weight of retarder (citric acid), 2.2 parts by weight of sodium lignin sulfonate water reducer, and 0.7 parts by weight of silicone defoamer.

[0053] (5) The rapid hardening sulphoaluminate cement, fine sand aggregate, inorganic filler, anti-carbonation agent and anti-thermal cracking agent are mixed and stirred for 2 minutes, and then the retarder, retarder and defoamer are added, and clean water is added according to a water-cement ratio of 0.44 and stirred evenly to obtain a sulphoaluminate cement-based repair material.

[0054] The 3d compressive strength, 7d strength retention rate and 28d strength retention rate of the sulphoaluminate cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The results are shown in Table 3.

[0055] Table 3

[0056] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 74.21MPa 99.53% 105.68%

[0057] Example 4

[0058] A preparation process of a marine concrete structure crack repair material comprises the following steps:

[0059] (1) Take 131 parts by weight of rapid hardening sulphoaluminate cement, 230 parts by weight of river sand fine aggregate with a particle size between 0.1 and 0.2 mm, 50 parts by weight of inorganic filler (including 30 parts by weight of fly ash and 20 parts by weight of silica fume), 0.2 parts by weight of retarder (borax), 2 parts by weight of polycarboxylate water reducer, and 0.5 parts by weight of silicone defoamer.

[0060] (2) The rapid hardening sulphoaluminate cement, fine sand aggregate and inorganic filler are mixed and stirred for 2 minutes, and then the retarder, setting retarder and defoamer are added, and clean water is added according to a water-cement ratio of 0.42 and stirred evenly to obtain a sulphoaluminate cement-based repair material.

[0061] The 3d compressive strength, 7d strength retention rate and 28d strength retention rate of the sulphoaluminate cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The results are shown in Table 4.

[0062] Table 4

[0063] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 66.73MPa 90.16% 79.27%

[0064] Example 5

[0065] A preparation process of a marine concrete structure crack repair material. Compared with the above-mentioned embodiment 1, the anti-carbonization agent of this embodiment is prepared by the following method:

[0066] (1) Add shellac to anhydrous ethanol and stir to form a 4% by mass shellac ethanol solution for later use.

[0067] (2) Spray the ethanolic shellac solution on the rolling tricalcium silicate particles (particle size 0.2-0.3 mm) at a material-liquid ratio of 1 g:1 ml. Continue rolling for 2 minutes after spraying, then continue rolling and heat to 70°C for 25 minutes. After completion, cool to room temperature to obtain a granular anti-carbonization agent for use.

[0068] The 3d compressive strength, 7d strength retention rate and 28d strength retention rate of the sulphoaluminate cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The results are shown in Table 5.

[0069] Table 5

[0070] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 64.92MPa 91.07% 82.11%

[0071] Example 6

[0072] A preparation process of a marine concrete structure crack repair material. Compared with the above-mentioned embodiment 2, the anti-carbonization agent of this embodiment is prepared by the following method:

[0073] (1) Shellac is added to anhydrous ethanol and stirred to form a 6% by mass shellac ethanol solution, and then 400-mesh calcium carbide slag powder is added and ultrasonically dispersed for 10 minutes to obtain a suspension for use, wherein the content of the calcium carbide slag powder is 0.25 g / ml.

[0074] (2) Spray the suspension in a rolling river sand (particle size 0.2-0.3 mm) at a solid-liquid ratio of 1 g:0.8 ml. Continue rolling for 2 minutes after spraying, then continue rolling and heat to 60°C for 35 minutes to dry. After completion, cool to room temperature to obtain a granular anti-carbonization agent.

[0075] The 3d compressive strength, 7d strength retention rate and 28d strength retention rate of the sulphoaluminate cement-based repair material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1. The results are shown in Table 6.

[0076] Table 6

[0077] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 70.87MPa 97.69% 88.56%

[0078] Example 7

[0079] A preparation process of a marine concrete structure crack repair material comprises the following steps:

[0080] (1) Take 140 parts by weight of rapid hardening sulphoaluminate cement, 250 parts by weight of machine-made sand fine aggregate with a particle size of 0.1-0.2 mm, 75 parts by weight of inorganic filler (calcium carbonate powder with a fineness of 200 mesh), 60 parts by weight of the anti-carbonization agent prepared in Example 3, 16.8 parts by weight of 80-mesh paraffin powder, 11.2 parts by weight of graphene, 0.3 parts by weight of retarder (citric acid), 2.2 parts by weight of sodium lignin sulfonate water reducer, and 0.7 parts by weight of silicone defoamer.

[0081] (2) The rapid hardening sulphoaluminate cement, fine sand aggregate, inorganic filler, anti-carbonization agent, paraffin powder and graphene are mixed and stirred for 2 minutes, and then the retarder, retarder and defoamer are added, and clean water is added according to a water-cement ratio of 0.44 and stirred evenly to obtain a sulphoaluminate cement-based repair material.

[0082] The 3d compressive strength, 7d strength retention rate and 28d strength retention rate of the sulphoaluminate cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The results are shown in Table 7.

[0083] Table 7

[0084] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 71.34MPa 98.13% 103.23%

[0085] Example 8

[0086] A preparation process of a marine concrete structure crack repair material comprises the following steps:

[0087] (1) Take 120 parts by weight of quick-hardening sulphoaluminate cement, 190 parts by weight of river sand fine aggregate with a particle size of 0.1-0.25 mm, 60 parts by weight of inorganic filler (including 40 parts by weight of fly ash and 20 parts by weight of 300-mesh slag powder), 45 parts by weight of the anti-carbonization agent prepared in Example 2, 23 parts by weight of 120-mesh paraffin powder, 0.1 parts by weight of retarder (sodium gluconate), 1.5 parts by weight of polycarboxylate water reducer, and 0.35 parts by weight of silicone defoamer.

[0088] (2) The rapid hardening sulphoaluminate cement, fine sand aggregate, inorganic filler, anti-carbonization agent and paraffin powder are mixed and stirred for 2 minutes, and then the retarder, retarder and defoamer are added, and clean water is added according to a water-cement ratio of 0.37 and stirred evenly to obtain a sulphoaluminate cement-based repair material.

[0089] The 3d compressive strength, 7d strength retention rate and 28d strength retention rate of the sulphoaluminate cement-based repair material prepared in this embodiment were tested using the same method as in the above-mentioned embodiment 1. The results are shown in Table 8.

[0090] Table 8

[0091] Performance Indicators 3d compressive strength 7d compressive strength retention rate 28d compressive strength retention rate Test value 69.22MPa 99.04% 101.81%

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A preparation process of a marine concrete structure crack repair material, characterized in that: The steps include: (1) Take the following raw materials: 120-140 parts by weight of sulphoaluminate cement, 190-250 parts by weight of fine aggregate, 50-75 parts by weight of inorganic filler, 45-60 parts by weight of anti-carbonation agent, 0.1-0.3 parts by weight of retarder, 1.5-2.2 parts by weight of water reducer, and 0.35-0.7 parts by weight of defoamer; mix the above raw materials evenly, add clean water, and stir evenly to obtain a repair material; wherein the anti-carbonation agent is prepared by the following method: (2) dissolving shellac in anhydrous ethanol, and then adding carbide slag powder and mixing to form a suspension; (3) Spraying the suspension on the rolling tricalcium silicate particles, and continuing to roll and heat to dry after uniform coating; after completion, the anti-carbonization agent in granular form is obtained.

2. The preparation process of the marine concrete structure crack repair material according to claim 1, characterized in that: In step (2), the mass fraction of shellac in the anhydrous ethanol is 3.5-6%.

3. The preparation process of the marine concrete structure crack repair material according to claim 1, characterized in that: In step (2), the content of calcium carbide slag powder in the suspension is 0.25-0.4 g / ml.

4. The preparation process of the marine concrete structure crack repair material according to claim 1, characterized in that: In step (2), the fineness of the calcium carbide slag powder is 300-400 mesh.

5. The preparation process of the marine concrete structure crack repair material according to claim 1, characterized in that: In step (3), the solid-liquid ratio of the tricalcium silicate particles to the suspension is 1 g: 0.8-1.1 ml.

6. The preparation process of the marine concrete structure crack repair material according to claim 1, characterized in that: In step (3), the particle size of the tricalcium silicate particles is 0.2-0.3 mm.

7. The preparation process of the marine concrete structure crack repair material according to claim 1, characterized in that: In step (3), the heating temperature is 60-70° C. and the heating time is 20-35 min.

8. The preparation process of the marine concrete structure crack repair material according to claim 1, characterized in that: In step (1), the raw materials also include 23-28 parts by weight of an anti-thermal cracking agent; the anti-thermal cracking agent is prepared by the following process: adding graphene to a heated and melted paraffin liquid, mixing well, cooling, and then crushing to obtain the anti-thermal cracking agent in powder form.

9. The preparation process of the marine concrete structure crack repair material according to claim 8, characterized in that: The mass ratio of the graphene to the paraffin liquid is 1:1.5-1.8, and the melting point of the paraffin does not exceed 60°C.

10. The preparation process of the marine concrete structure crack repair material according to claim 8, characterized in that: The fineness of the anti-thermal cracking agent is 80-120 meshes.

11. The preparation process of the marine concrete structure crack repair material according to any one of claims 1 to 10, characterized in that: In step (1), the fine aggregate includes at least one of river sand and machine-made sand.

12. The preparation process of the marine concrete structure crack repair material according to any one of claims 1 to 10, characterized in that: In step (1), the inorganic filler includes at least one of fly ash, silica fume, slag powder, calcium carbonate powder and kaolin.

13. The preparation process of the marine concrete structure crack repair material according to claim 12, characterized in that: The fineness of the slag powder, calcium carbonate powder and metakaolin is between 200 and 300 meshes.

14. The preparation process of the marine concrete structure crack repair material according to any one of claims 1 to 10, characterized in that: In step (1), the retarder includes at least one of borax, citric acid, sodium gluconate and tartaric acid.

15. The preparation process of the marine concrete structure crack repair material according to any one of claims 1 to 10, characterized in that: In step (1), the water reducer includes at least one of a polycarboxylic acid water reducer, a naphthalene-based water reducer, and a lignin sulfonate-based water reducer.

16. The preparation process of the marine concrete structure crack repair material according to any one of claims 1 to 10, characterized in that: In step (1), the defoaming agent includes at least one of a silicone defoaming agent and a polyether defoaming agent.

17. The preparation process of the marine concrete structure crack repair material according to any one of claims 1 to 10, characterized in that: In step (1), the clean water is added according to a water-cement ratio of 0.37-0.44.

Citation Information

Patent Citations

  • Solid-waste-based high-iron sulphoaluminate maritime work cementing material as well as preparation method and application thereof

    CN113698117A

  • In-situ high-strength carbonization gradient material as well as preparation method and application thereof

    CN116102329A